Developmental Screening Tools for Motor Developmental Delay in High Risk Preterm Infants - Ramachandran, Selvam; Dutta, Sudip (Journal of Nepal Paediatric Society, 2016)
The preterm very low birth weight infants are at high risk of motor developmental delays. The developmental screening tools used by health professionals in pediatric practice serves several purposes viz. as a discriminative screening tool to identify the developmental delay in such high risk infants; as an evaluation tool to quantify the levels of functional skills achieved; as a prognostic tool to quantify the changes in levels of functional skills following specific developmental care interventions and as a predictive tool to predict the quantum of existing or impending neuro-developmental disability in high risk infants. Thus developmental screening tools serves as an integral part of early intervention programs. Such screening tools also serve as program evaluation strategy in quantifying the efficacy of early developmental care intervention programs. This review is aimed at describing the properties of developmental screening tools for motor developmental delay in preterm infants. J Nepal Paediatr Soc 2015;35(2):162-167